Clinical outcomes over 2 years following arthroscopic ankle lateral ligament repair with os subfibulare - Shohei Sano; Noriyuki Kanzaki; Kiminari Kataoka; Koji Nukuto; Tetsuya Yamamoto; Yuta Nakanishi; Kyohei Nishida; Kanto Nagai; Yuichi Hoshino; Takehiko Matsushita; Ryosuke Kuroda (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology)
Background: There are reports indicating that between 10 and 38.5 % of patients with chronic lateral ankle instability (CLAI) have an os subfibulare. In cases where CLAI accompanied by os subfibulare is resistant to conservative treatment, surgery may be necessary; however, there is no consensus on the most appropriate surgical method. We report outcomes of arthroscopic lateral ligament repair for chronic lateral ankle instability with os subfibulare at our hospital, followed for over 2 years post-operatively. Methods: We reviewed 33 patients (39 ankles) whom underwent arthroscopic lateral ankle ligament repair (ALLR) for CLAI and followed for at least 2 years post-operatively between November 2015 and May 2020. Patients were classified into two groups: a group with os subfibulare (ossicle group) and a group without os subfibulare (non-ossicle group), based on the presence of an os subfibulare on pre-operative plain radiographs. ALLR surgeries were performed without resection of the os subfibulare in ossicle group. Clinical outcomes were assessed using the Japanese Society for Surgery of the Foot (JSSF) scale and the Self-administered Foot Evaluation Questionnaire (SAFE-Q). In addition, the bone-union rate was evaluated by using plain computer tomography in the ossicle group. Results: There were significant improvements in the mean total JSSF scale scores from pre-operative to post-operative measurements in both the ossicle and non-ossicle groups. The mean scores for pain and related symptoms, foot function and activities of daily living, social functioning, shoe-related, and general health and well-being subscales of the SAFE-Q also showed significant improvements in both groups. There were no significant differences between the post-operative ossicle and non-ossicle groups regarding the JSSF scale scores or the SAFE-Q subscale scores. In the ossicle group, the bone-union rate was 14.3 % (2 of 14 ankles), but no symptom recurrence was observed. Conclusion: The 2 years outcomes of arthroscopic lateral ligament repair for chronic lateral ankle instability with os subfibulare revealed good results and no symptom recurrence.